Kebijakan Negara-Negara Eropa Sebagai Respon terhadap Gerakan Femen - Putra, Ferdian Ahya Al; Prakoso, Septyanto Galan (Spirit Publik: Jurnal Administrasi Publik, 2023)
Femen is an international women's movement with bare-chested acts and body paintings with slogans and flowers as symbols of protest. The history of this movement began in 2008 which was carried out in Ukraine. As a movement group, Femen has a vision to oppose patriarchal values and culture, especially those that develop in Europe. This article will analyze the policy of several countries as responses to the Femen movement based on the perspective of 4 waves of feminism and the concept of checks and balances. While the method used in this study is descriptive qualitative with literature study techniques to obtain data. The results of the study show that most of the parties involved, including countries in the European Union, do not provide policies or special treatment for the Femen movement, but will take firm action in accordance with applicable law if the actions of Femen members have exceeded the limit. In this case, this firm attitude towards Femen is applied when the protest action that is carried out causes anxiety and disrupts the course of an agenda within the European Union. Femen often targets public places, one of which is a place of worship, to give a shocking effect that can attract the world's attention. This method is a way to get the world's attention to them, so that they can voice their opinions more freely in the hope that the international community can empathize with their aspirations. Femen's actions that are bare-chested in carrying out their actions often cause uproar in society. Instead of getting public empathy, their actions actually have an impact on the negative stigma attached to them.